Penanggulangan kemiskinan dalam perspektif Al-Qur’an dan Hadis - Aditya, M. Dwi Rizki; Hakim, Ali Rahman; Faisol, Faisol (Maliki Interdisciplinary Journal, 2024)
The alleviation of poverty from the perspective of the Quran and Hadith offers a holistic and comprehensive approach encompassing various aspects of social and economic life. Fundamental principles in Islamic teachings, such as zakat, sadaqah, infaq, and social justice, provide a robust foundation for building a more equitable and prosperous society. The implementation of zakat plays a crucial role in wealth redistribution and reducing economic disparities, while sadaqah and infaq strengthen social bonds and mitigate economic inequalities. The principles of justice and equality emphasize the importance of protecting individual rights and ensuring fair wealth distribution. In the modern context, Islamic financial institutions, government programs, social organizations, and community initiatives can apply these Islamic principles to combat poverty. This approach not only addresses material needs but also empowers individuals through education, skill enhancement, and the creation of economic opportunities. Therefore, Islamic teachings can serve as a valuable guide in the global efforts to tackle poverty and injustice.